Assessing the Quality of Sustainability Disclosures in Lithuania’s Largest Electronic Communications Companies - Račaitė, Sabina (Buhalterinės apskaitos teorija ir praktika, 2026)
This study examines the importance and regulatory framework of sustainability information disclosure, with particular emphasis on the requirements established by the European Union. Based on the European Sustainability Reporting Standards (ESRS), a methodology for assessing the scope and quality of sustainability information disclosure was developed. The study presents the results of an analysis of sustainability reports published by the largest electronic communications companies in Lithuania during the period 2022–2024. The findings reveal that the companies disclosed 91% of the assessed sustainability information, indicating a consistently high level of disclosure throughout the study period. Across the ESG dimensions, social responsibility topics were disclosed most extensively, particularly those related to own workforce, workers in the value chain, consumers, and end-users. Within the environmental dimension, climate change disclosures showed the most consistent improvement, reaching the maximum disclosure level in 2024, while resource use and circular economy disclosures remained at a high level throughout the period. Disclosures concerning pollution, water and marine resources, and biodiversity were provided only by UAB „Tele2“. In the governance dimension, the business conduct topic was analysed, and its disclosure level increased steadily between 2022 and 2024. The quality of sustainability information improved across all companies during the study period and was assessed as sufficient. Relevance and understandability received the highest evaluations, whereas comparability and verifiability remained the weakest areas. These findings indicate that companies provide relevant, clear, and faithful representation on sustainability. However, there are still gaps in terms of comparable performance indicators, methodological explanations, and longitudinal data.
Keywords: sustainability reporting; quality of sustainability disclosure; sustainability; non-financial reporting; ESRS